The quality improvement of interaction indicators in Arabic language learning for higher education - Bahruddin, Uril (Universitas Muhammadiyah Malang, 2021)
The success of learning Arabic is largely determined by the quality of interaction in learning. This article aims to describe (1) Increasing speaking skills through Arabic learning interactions, (2) Increasing cooperation through learning interactions, and (3) Increasing solidarity through learning interactions. So far, this aspect has been neglected in existing studies. This research approach is qualitative with the type of case study research. The research data were collected through interviews, observation, and documentation. Data analysis starts from data collection to concluding. The results showed that the improvement of speaking skills was carried out by selecting interesting topics, using familiar vocabulary among students, and giving them motivation. In terms of increasing cooperation, this is done by giving joint assignments, joint corrections, making videos, and playing roles. Meanwhile, in the context of increasing solidarity, the activities carried out are by instilling a sense of brotherhood, group work, and giving responsibility to help each other.